(untitled) (Gaceta Técnica, 2024)
The construction process is fundamental in the construction of civil works, the vision and planning must be correctly defined before carrying out a structural work in the field, especially if they are works that require a more detailed process such as essential works. In this article, a structural analysis of the construction process involved in an essential structure was carried out, which has the following characteristics: 6 levels, 9 m spans and a mezzanine height of 4,50 m. According to these characteristics, a modeling of the construction process was carried out by applying a formwork, clearing and stripping procedure. With the help of computational packages such as ETABS, modeling has been carried out for the analysis of the structure in relation to the auxiliary elements that exist in it, in this case the props, resulting in the behavior of the structure according to the load steps used in the program, thus, obtaining that the loads of Model 2 are 3-6 times greater than Model 1, as well as the most critical value of 135,51 kN obtained in the load step N°2 of Model 2